O književnoj životinji u Kanižlićevoj Svetoj Rožaliji - Šundalić, Zlata; Ćurak, Silvija; BLAŽEVIĆ KREZIĆ, Vera (Anafora, 2024)
The paper deals with the analysis of the literary animal in the poem Saint Rosalia written by the Jesuit monk Antun Kanižlić from Požega (Požega, 1699 – Požega, 1777). In the context of the Croatian baroque religious poems (Ivan Gundulić, Suze sina razmetnoga; Ivan Bunić Vučić, Mandalijena pokornica; Ignjat Đurđević, Uzdasi Mandalijene pokornice), along with previously identified differences in the motives, topics, structure, meter, and prayer as the secondary genre, Kanižlić’s poem is distinctive in the depiction of the animal world. The presence of the animal species in the given poems is not consistent: it is the least frequent in Bunić’s Mandalijeni pokornici (10), almost the same in Uzdasi Mandalijene pokornice (21) and in Suze sina razmetnoga (22), while it is the most frequent in Saint Rosalia (61). The analysis of the Kingdom of Animalia in Rosalia showed that fauna is the richest in the first section, by a third less in the second and third sections, while in the fourth one, it reflects only a third of the first section. In its primary meanings (e.g. birds), the richer animal world can be mainly noticed in those poems in which the Rococo „external eye“ dominates (the first and second poems, particularly in the depictions of Rosalia’s enchantment with nature’s beauty, its sounds, and movements). Towards the end of the poem the Baroque „internal eye“ is gradually less open to the animal world, whereas different poetic and moral symbolism emerging from the figurative correspondences with particular moral and theological concepts is more frequent.